THE EFFECTS OF SUBSTANCE ABUSE ON CRIME RATES: A CASE STUDY OF BUSIA MUNICIPALITY - OCHIENG ALEX (My University, 2024)
ABSTRACT The study looked at a number of issues related to substance abuse and the rise in crime in Busia Municipality. This study examines the effect substance abuse on crime rates, the consequences of substance abuse, and the ways in which different agencies and stakeholders can work together to address the issue of substance abuse in Busia Municipality. The study also looked at the different kinds of drugs that the people in Busia Municipality were consuming, including cocaine, tobacco, and hard liquor. Additionally, a number of characteristics that lead Busia Municipality residents to engage in substance misuse were examined, with the primary ones being stress, peer pressure, drug accessibility, and addiction are a few more. After examining the causes, the study looked at how drug usage affected young people's health, including brain deformities and HIV/AIDS. A number of approaches to addressing the issue of substance misuse were also presented, including developing appropriate programs that encourage people to participate and stay active rather than sit about. The findings showed that materials that are indicative of alcohol include beers and hard liquors such coffee spirit and torero. The most mistreated were Sanyuka, Empire, and magnificence, among others. After that came cocaine, oris, and tobacco. With regard to all of these drugs, several strategies for handling substance abuse were described. Even though the researcher had to deal with a number of obstacles, suggestions were made, like conducting a similar study in which parents are interviewed as some may be the cause of the youth's involvement in substance addiction. When respondents refused to provide information, the researcher attempted to get information by using tactful and convincing language while also assuring them that the study was conducted for academic interests.